Financial Integration, Growth, and Volatility - Epaulard, Anne (IMF Working Papers; Working Paper ;, 2005)
The aim of this paper is to evaluate the welfare gains from financial integration for developing and emerging market economies. To do so, we build a stochastic endogenous growth model for a small open economy that can (i) borrow from the rest of the world, (ii) invest in foreign assets, and (iii) receive foreign direct investment (FDI). The model is calibrated on 32 emerging market and developing economies for which we evaluate the upper bound for the welfare gain from financial integration. For plausible values of preference parameters and actual levels of financial integration, the mean welfare gain from financial integration is about 10 percent of initial wealth. Compared with financial autarky, actual levels of financial integration translate into slightly higher annual growth rates (around 0.4 percentage point per year.).